Visual Acuity of Four-Wheeled Public Transport Drivers in Jatinangor - Feranika, Feranika; Farenia, Reni; Ratnaningsih, Nina (Althea Medical Journal, 2018)
Background: The number of motor vehicles usage is increasing every year, along with the increasing prevalence of motor vehicle accidents, and mortality due to traffic accidents in 2010. The driver’s visual impairment is one factor that affects this phenomenon. In Indonesia there are regulations regarding the minimum requirements for visual acuity in order to get a driving license. However, data of driver’s visual acuity have not been obtained yet. This study aimed to assess the public transport (angkot) driver’s visual acuity. Thus, the regulation and evaluation of the minimum requirements for a driver’s visual acuity can be applied optimally. Methods: This study used the categorical descriptive method with cross sectional design to assess visual acuity for four-wheeled motor vehicle (angkot) drivers in Jatinangor using RAAB E chart and pinhole. The variable that was described in this study was the visual acuity of 4-wheeled motor vehicle drivers in Jatinangor.Results: Results showed 86.5% of drivers fulfilled the minimum requirements of visual acuity for driving. Meanwhile, the rest did not fulfill the minimum requirements of visual acuity for driving.Conclusions: Most of the public transport drivers have already fulfilled the minimum requirement of visual acuity for driving. However the minimum requirement of visual acuity for drivers has not been implemented optimally since there were drivers who have not performed an eye examination when taking and extending their driving license.